Predicting complex acute wound healing in patients from a wound expertise centre registry: a prognostic study - Ubbink, Dirk T (Int Wound J, 2013)
It is important for caregivers and patients to know which wounds are at risk of prolonged wound healing to enable timely communication and treatment. Available prognostic models predict wound healing in chronic ulcers, but not in acute wounds, that is, originating after trauma or surgery. We developed a model to detect which factors can predict (prolonged) healing of complex acute wounds in patients treated in a large wound expertise centre (WEC). Using Cox and linear regression analyses, we determined which patient‐ and wound‐related characteristics best predict time to complete wound healing and derived a prediction formula to estimate how long this may take. We selected 563 patients with acute wounds, documented in the WEC registry between 2007 and 2012. Wounds had existed for a median of 19 days (range 6–46 days). The majority of these were located on the leg (52%). Five significant independent predictors of prolonged wound healing were identified: wound location on the trunk [hazard ratio (HR) 0·565, 95% confidence interval (CI) 0·405–0·788; P = 0·001], wound infection (HR 0·728, 95% CI 0·534–0·991; P = 0·044), wound size (HR 0·993, 95% CI 0·988–0·997; P = 0·001), wound duration (HR 0·998, 95% CI 0·996–0·999; P = 0·005) and patient's age (HR 1·009, 95% CI 1·001–1·018; P = 0·020), but not diabetes. Awareness of the five factors predicting the healing of complex acute wounds, particularly wound infection and location on the trunk, may help caregivers to predict wound healing time and to detect, refer and focus on patients who need additional attention.